Effect of acupuncture for disorders of consciousness in patients with stroke: A systematic review and meta-analysis - Huang, Zhibin; Chen, Yuning; Xiao, Qilan; Kuang, Weichuan; Liu, Kun; Jiang, Ye; Wen, Xi; Qin, Weiting; Liu, Yue; Liu, Tong (Frontiers in Neurology, 2022)
Background Disorder of consciousness (DOC) is frequent in patients with stroke, which is the second most common cause of death and a leading cause of disability. Acupuncture has been used as a curative method for DOC treatment in China. Nevertheless, no critical systematic review of acupuncture's effect on DOC has been published. This review aims to evaluate the present evidence regarding the efficacy of acupuncture for DOC after stroke. Methods Seven databases were searched from their inception to November 1, 2021, containing three English databases (PubMed, Embase, and Cochrane Central Register of Controlled Trials) and four Chinese databases (CNKI, CBM, VIP, and Wanfang Database). The primary outcomes comprise the Glasgow Coma Scale (GCS) and Glasgow Outcome Scale (GOS) before and after treatment. Secondary outcomes involve resuscitation rate, resuscitation time, and adverse events. Data synthesis was calculated by RevMan (V.5.4.1) software. According to the Cochrane Handbook, methodological quality was assessed with the risk of bias tool 2.0 (RoB2). Results Seventeen studies containing 1,208 patients were eventually included in our review. Overall, most trials were rated as high or had some concerns regarding the risk of bias. GCS was reported in 16 trials, and a meta-analysis showed that GCS improvement in the acupuncture group was greater than in the non-acupuncture group (MD 1.45, 95% CI 0.94–1.97, P < 0.0001). One trial reported that GOS improvement in the acupuncture plus medication group was greater than in the medication group (MD 0.58, 95% CI 0.11–1.05, P = 0.01). Another study reported that acupuncture plus medication was statistically more effective in shortening resuscitation time than medication alone (MD−0.89, 95% CI −1.53 to −0.25, P = 0.006). Four trials reported that the resuscitation rate in the acupuncture group was higher than without acupuncture intervention (RR 1.68, 95% CI 1.30–2.18, I2 0%, P = 0.39). Adverse events were reported in two studies, with one case in the acupuncture group suffering from subcutaneous hematoma. Conclusion Acupuncture may improve consciousness level, increase the resuscitation rate, and shorten resuscitation time for post-stroke patients with DOC. Adverse events from acupuncture were rare, tolerable, and recoverable. However, the results should be interpreted cautiously, and more rigorous RCTs with better methodology are warranted. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=289802, identifier 289802.